Communication Skills in Software Engineering: A Multivocal Review - Rabelo, Dannilo; Peres, Deisy; Dias, Emmanuel; Rocha, Thayssa; Freitas, Enne Rebeca de; Gama, Kiev; Pinto, Gustavo (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2026: Anais do XI Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2026.22120, 2026)
Communication skills are increasingly recognized as essential in Software Engineering, yet discussions about them remain fragmented across academic and gray literature. This fragmentation is problematic because it limits a broader understanding of how communication is valued, taught, and applied in both educational and professional settings. Through a multivocal literature review, we found strong convergence between academic and gray sources in treating communication as a core competency, while also identifying differences in emphasis, with academia focusing on conceptualization and empirical evidence and gray literature stressing practical consequences and emerging industry practices.